Bioactive Molecules of Tea as Potential Inhibitors for RNA-Dependent RNA Polymerase of SARS-CoV-2 - Bhardwaj, Vijay Kumar; Singh, Rahul; Sharma, Jatin; Rajendran, Vidya; Purohit, Rituraj; Kumar, Sanjay (Frontiers in Medicine, 2021)
The coronavirus disease (COVID-19), a worldwide pandemic is caused by the severe acute respiratory syndrome-corona virus-2 (SARS-CoV-2). At this moment in time, there are no specific therapeutics available to combat COVID-19. Drug repurposing and identification of naturally available bioactive molecules to target SARS-CoV-2 are among the key strategies to tackle the notorious virus. The enzyme RNA-dependent RNA polymerase (RdRp) performs a pivotal role in replicating the virus. RdRp is a prime target for Remdesivir and other nucleotides analog based antiviral drugs. In this study, we showed three bioactive molecules from Tea (epicatechin-3,5-di-O-gallate, epigallocatechin-3,5-di-O-gallate, and epigallocatechin-3,4-di-O-gallate) that showed better interaction with critical residues present at the catalytic center and NTP entry channel of RdRp than antiviral drugs Remdesivir and Favipiravir. Our computational approach to identify these molecules included molecular docking studies, followed by robust molecular dynamics simulations. All the three molecules are readily available in Tea and could be made accessible along with other medications to treat COVID-19 patients. However, these results require validation by further in-vitro and in-vivo studies.